Multi-material topology optimization using Wachspress interpolations for designing a 3-phase electrical machine stator - Cherrière, Théodore; Laurent, Luc; Hlioui, Sami; Louf, François; Duysinx, Pierre; Geuzaine, Christophe; Ben Ahmed, Hamid; Gabsi, Mohamed; Fernández, Eduardo (Structural and multidisciplinary optimization, 2022)
This work uses multi-material topology optimization (MMTO) to maximize the average torque of a 3-phase permanent magnet synchronous machine (PMSM). Eight materials are considered in the stator: air, soft magnetic steel, three electric phases, and their three returns. To address the challenge of designing a 3-phase PMSM stator, a generalized density-based framework is used. The proposed methodology places the prescribed material candidates on the vertices of a convex polytope, interpolates material properties using Wachspress shape functions, and defines Cartesian coordinates inside polytopes as design variables. A rational function is used as penalization to ensure convergence towards meaningful structures, without the use of a filtering process. The influences of different polytopes and penalization parameters are investigated. The results indicate that a hexagonal-based diamond polytope is a better choice than the classical orthogonal domains for this MMTO problem. In addition, the proposed methodology yields high-performance designs for 3-phase PMSM stators by implementing a continuation method on the electric load angle.